Impact of Celebrity Endorsement on Consumers Buying Behavior - Amir Adam and Nazish Hussain, Muhammad (British Journal of Marketing Studies, 2017)
This research is conducted on “impact of celebrity endorsement on consumer’s buying behavior”; this behavior judges the purchase intention of consumers in the field of cosmetics, this research only focuses on the buying intention of the female segment. Celebrity endorsement is made up of four main pillars that are credibility, attractiveness, product matchup and lastly meaning transfer. All these four elements combine to make up celebrity endorsement. The findings of this research report shows that the element of credibility (which is composed of expertise and trustworthiness) of the celebrity positively affects consumers intention to purchase cosmetics. Celebrities also transfer meanings to the product that positively influences consumer’s intention to buy cosmetics. This meaning transferred indicates that consumers start accepting that celebrity endorsed cosmetics makes them feel classy and glamorous and also perceive such cosmetics as a symbol of status. This research also shows that people get more attracted towards celebrity endorsed advertisements than the ones that doesn’t have celebrities into them which ultimately leads them to recall the products (cosmetics) much easier because celebrities appeared into those advertisements.